Biofuels : alternative feedstocks and conversion processes - Pandey, Ashok (Academic Press, 2011)
Global concern for energy security and environmental protection has put great emphasis on the search for alternative energy sources, particularly for the transport sector. Biofuels have emerged as a highly promising source of alternative energy, and have drawn global R & D for their production using biomass. With the increasing worldwide demand of energy along with the depletion of conventional fossil fuel reserves, there has been growing global interest in developing alternative sources of energy. There has also been concern in growing economies regarding energy security. Biofuels offer much promise on these frontiers. In addition to the above, they also have a reduced environmental impact in comparison to fossil fuels. Biofuels provides state-of-the-art information on the status of biofuel production and related aspects.